Increased white matter radial diffusivity is associated with prefrontal cortical folding deficits in schizophrenia. (30th March 2017) - Schultz, C. Christoph; Wagner, Gerd; Schachtzabel, Claudia; Reichenbach, Jürgen R.; Schlösser, Ralf G.M.; Sauer, Heinrich; Koch, Kathrin
Abstract: The neuronal underpinnings of cortical folding alterations in schizophrenia remain unclear. Theories on the physiological development of cortical folds stress the importance of white matter fibers for this process and disturbances of fiber tracts might be relevant for cortical folding alterations in schizophrenia. Nine-teen patients with schizophrenia and 19 healthy subjects underwent T1-weighted MRI and DTI. Cortical folding was computed using a surface based approach. DTI was analyzed using FSL and SPM 5. Radial diffusivity and cortical folding were correlated covering the entire cortex in schizophrenia. Significantly increased radial diffusivity of the superior longitudinal fasciculus (SLF) in the left superior temporal region was negatively correlated with cortical folding of the left dorsolateral prefrontal cortex (DLPFC) in patients, i.e. higher radial diffusivity, as an indicator for disturbed white matter fiber myelination, was associated with lower cortical folding of the left DLPFC. Patients with pronounced alterations of the SLF showed significantly reduced cortical folding in the left DLPFC. Our study provides novel evidence for a linkage between prefrontal cortical folding alterations and deficits in connecting white matter fiber tracts in schizophrenia and supports the notion that the integrity of white matter tracts is crucial for intact morphogenesis of the cortical folds. Highlights: Combined DTI and cortical folding analysis in patients with schizophrenia. Higher radial diffusivity of the SLF is associated with reduced prefrontal cortical folding. Findings support tension based models of gyrification.